Pemanfaatan Web Design Untuk Meningkatkan Pemasaran Pondok Pical Sate Ima - Rasyadah Fadhillah; Riva Nurul Hasanah; Sularno Sularno; Zulfitri Yani (CV. ITTC INDONESIA, 2025)
This Project-Based Learning project aims to provide an understanding of the creative implementation of electronic or online sales at Pondok Pical Sate Ima to make the marketing process more effective and efficient. The research method used was qualitative, with data sourced from Pondok Pical Sate Ima, one of the MSMEs in Padang City. This research focused on creating a marketplace using HTML code as a form of implementing digital technology in the sales system. Data collection techniques were conducted through surveys and interviews, using mobile phones for documentation and writing materials for taking notes as needed. The results indicate that Pondok Pical Sate Ima has a desire to innovate and adapt to new technologies creatively and innovatively, thus managing risks and competing with technological developments in today's society.